Investigation on the polyethylene glycol based composite phase change materials with coating flame-retardant for battery thermal management - Tingyu Wang; Jian Deng; Jiexin Du; Wensheng Yang; Yueyu Zeng; Tingting Wu; Zhonghao Rao; Xinxi Li (Case Studies in Thermal Engineering)
Pure battery-powered ships and vehicles have been rapidly developed as green transportation, the safety of battery packs as the only energy source has attracted much attention. Herein, an innovative polyethylene glycol (PEG) based solid-solid phase change materials (SSPCM) with high flame-retardant properties has been prepared and utilized in the battery module. Initially, PEG has been polymerized with diphenylmethane diisocyanate (MDI) to constrain the solid-solid phase transition process by forming covalent bonds to improve thermal stability, which is eutectic transformation with hexacetyl alcohol (HA) by synergistic effect to further to increase phase change latent heat. Not only that, hexachlorocyclotriphosphazene (HCCP) is coated on the surface of the SSPCM to improve the flame-retardant level. The PHEH-10 with 10 % HCCP exhibits latent heat with 146.65J/g and high flame-retardant properties with UL94-V0. Additionally, the thermal management effect of the battery module with PHEH-10 has significantly improved. Even at 2C discharge rate, the maximum temperature and temperature difference of the square battery module are controlled within 50.63 °C and 5.61 °C, respectively. Thus, this research will provide an efficient and feasible thermal safety protecting strategy for battery packs in the application of pure battery-powered transport vehicles.